已知:a-b/1+ab+c-d/1+cd=0,求证:a-d/1+ad+c-b/1+cb=a+c/1-ac+b+d/bd-

1个回答

  • 一、证明:(a-d)/(1+ad)+(c-b)/(1+cb)=0.

    ∵(a-b)/(1+ab)+(c-d)/(1+cd)=0,

    ∴(a-b)(1+cd)+(c-d)(1+ab)=0,

    ∴(a+acd-b-bcd)+(c+abc-d-abd)=0,······①

    ∴(a-d+abc-bcd)+(c-b+acd-abd)=0,

    ∴[(a-d)+cb(a-d)]+[(c-b)+ad(c-b)]=0,

    ∴(a-d)(1+cb)+(c-b)(1+ad)=0,

    ∴(a-d)/(1+ad)+(c-b)/(1+cb)=0.

    二、证明:(a+c)/(1-ac)+(b+d)/(bd-1)=0.

    由①,得:(a+c-bcd-abd)+(-b-d+acd+abc)=0,

    ∴[(a+c)-bd(a+c)]+[-(b+d)+ac(b+d)]=0,

    ∴(a+c)(1-bd)+(b+d)(ac-1)=0,

    ∴(a+c)/(1-ac)+(b+d)/(bd-1)=0.